Central Auditory Processing Disorder Profile in Premature and Term Infants - Amin, Sanjiv B.; Orlando, Mark; Monczynski, Christy; Tillery, Kim (American Journal of Perinatology, 2015)
Objective The aim of this study is to compare central auditory processing disorder (CAPD) profile between children born prematurely and at term.Methods A retrospective study involving children 7 to 13 years of age who were referred for CAPD evaluation over the past 3 years. Parental reports and medical records were used to collect information. Children with a score ≥ two standard deviations below the mean for at least one ear on at least two different CAPD tests were considered to have CAPD.Results A total of 82 children were evaluated for CAPD of which 22 met exclusion criteria, resulting in 60 children with CAPD (15 premature and 45 term). Premature children had higher prevalence of cesarean section delivery and neonatal jaundice compared with term children. Premature children had a higher total number of failed CAPD tests compared with the term children. Among CAPD tests, there was an increased frequency of abnormal Phonemic Synthesis test (PST) and decreased frequency of abnormal Staggered Spondaic Word test (SSW) among premature children compared with term children.Conclusion Premature children differ in CAPD profile compared with term children. Findings suggest possible etiological differences for CAPD such as jaundice or differential susceptibility of premature children for altered PST and SSW performance when compared with the term children.
Keywords: speech and language delay; central auditory nervous system; jaundice; attention deficit hyperactivity disorder